Antibiotic Stewardship Strategies and Their Association With Antibiotic Overuse After Hospital Discharge: An Analysis of the Reducing Overuse of Antibiotics at Discharge (Road) Home Framework . (10th February 2022) - Vaughn, Valerie M; Ratz, David; Greene, M Todd; Flanders, Scott A; Gandhi, Tejal N; Petty, Lindsay A; Huls, Sean; Feng, Xiaomei; White, Andrea T; Hersh, Adam L
Abstract: Background: Strategies to optimize antibiotic prescribing at discharge are not well understood. Methods: In fall 2019, we surveyed 39 Michigan hospitals on their antibiotic stewardship strategies. The association of reported strategies with discharge antibiotic overuse (unnecessary, excess, suboptimal fluoroquinolones) for community-acquired pneumonia (CAP) and urinary tract infection (UTI) was evaluated in 2 ways: (1) all strategies assumed equal weight and (2) strategies were weighted based on the ROAD (Reducing Overuse of Antibiotics at Discharge) Home Framework (ie, Tier 1—Critical infrastructure, Tier 2—Broad inpatient interventions, Tier 3—Discharge-specific strategies) with Tier 3 strategies receiving the highest weight. Results: Between 1 July 2017 and 30 July 2019, 39 hospitals with 20 444 patients (56.5% CAP; 43.5% UTI) were included. Survey response was 100%. Hospitals reported a median (interquartile range [IQR]) 12 (9–14) of 34 possible stewardship strategies. On analyses of individual stewardship strategies, the Tier 3 intervention, review of antibiotics prior to discharge, was the only strategy consistently associated with lower antibiotic overuse at discharge (adjusted incident rate ratio [aIRR] 0.543, 95% confidence interval [CI]: .335–.878). On multivariable analysis, weighting by ROAD Home tier predicted antibiotic overuse at discharge for both CAP and UTI. For diseases combined, having more weighted strategies was associated with lower antibiotic overuse at discharge (aIRR 0.957, 95% CI: .927–.987, per weighted intervention); discharge-specific stewardship strategies were associated with a 12.4% relative decrease in antibiotic overuse days at discharge. Conclusions: The more stewardship strategies a hospital reported, the lower its antibiotic overuse at discharge. However, Tier 3, or discharge-specific strategies, appeared to have the largest effect on antibiotic prescribing at discharge. Abstract : We used the Reducing Overuse of Antibiotics at Discharge Home framework to evaluate strategies to improve discharge antibiotic use across 39 hospitals. The more stewardship strategies reported, the lower antibiotic overuse at discharge, with discharge-specific strategies having the greatest effect.